Implementasi Transportasi Publik dalam Mendukung Terwujudnya Kota dan Permukiman Berkelanjutan - Dehya Al Fathurizqiyah; Corree Nathalia Tarigan; Trias Meiva Aulia; Deana Amelinda Kriswanto; Shahibah Yuliani (Jurnal Sains dan Teknologi, 2026)
The rapid population growth in urban areas has caused various complex problems, such as congestion, air pollution, and the high use of private vehicles, so that it becomes a challenge in realizing sustainable cities and settlements. Public transportation is present as one of the solutions in overcoming these problems because it can increase community mobility and reduce negative impacts on the environment. This study aims to analyze the implementation of Mass Rapid Transit (MRT), Light Rail Transit (LRT), TransJakarta, and Electric Rail Trains (KRL) in supporting the achievement of SDGs 11 Sustainable Cities and Settlements. This study uses a descriptive qualitative method with a literature study approach. The results show that the MRT and KRL contribute to efforts to reduce carbon emissions and congestion, TransJakarta excels in the aspect of cost affordability while the LRT plays a role in improving urban connectivity efficiently. Thus, public transportation palas an important role in realizing sustainable cities and settlements with the integration between modes of public transportation which is the main factor in supporting the achievement of SDGs 11 optimally.